Development and welfare indicators - Birla Institute of Scientific Research Economic Research (New Delhi, 1982)
The present study tries to focus on the multi dimensional nature of development involving changes in national and per capita incomes, improvement in the health of populace as reflected in the rise in the life expectancy, increase in literacy rates, changes in the pace and pattern of population growth and structural shifts away from agriculture in terms of employment. While dealing with the inadequacies of the GNP concept in measuring the totality of development, the author has refined the composite index (also called physical quality of life index) by incorporating two additional indicators relating to demographic and structural conditions in an economy which are of paramount significance in the developmental process. It reveals that temporal variations in the physical quality of life have occurred in consonance with changes in the rate of growth of per capita income in most of the countries under consideration even though they are not linearly related in the short run. Thus, a judicious use of national income statistics and the composite index would be a meaningful way more of looking at the performance of developing economies like India rather than the use of each one in isolation.
Keywords: Economic development-India